IMPLEMENTASI METODE FIFO PADA SISTEM PEMESANAN E-TIKET LOMBA BURUNG BERKICAU BERBASIS WEB - Satrio; Emilya Ully Artha; Maimunah (Universitas Palangka Raya, 2022)
Gantangan Jimjog, which is located in the Ponalan Vegetable Market, Muntilan, Magelang Regency, is one of the most crowded bird competitions in the Magelang area. Gantangan Jimjog is still using the manual system in booking tickets. Bird competition participants must first look for bird competition brochures on social media to view information on the chirping bird competition and place an order for tickets by contacting by telephone and it is possible that more than one participant can order the same hanger number. In this study, a web-based bird competition ticket booking system was made at Jimjog by applying the FIFO method. The FIFO method is applied in determining the queue for ordering race tickets based on the customer who is the first to pay, then the first one is given a hanger number according to what was ordered according to the existing quota. The ticket booking system that has been built can increase the time efficiency and productivity of Gantangan Jimjog and make it easier for participants to get information on the availability of bushel numbers.